PENINGKATAN KEPERCAYAAN DIRI SISWA TERHADAP MATEMATIKA DENGAN MENGGUNAKAN PENDEKATAN CTL (REACT) - Malik Ibrahim (Universitas Islam Negeri (UIN) Mataram, 2018)
The current study aims to describe the effectiveness of CTL approach (REACT) to improve students' self confidence in mathematics. It is a classroom action research (PTK). The subjects of the study were students of grade VIII MTs Nurul Ihsan Sukarara in the academic year 2017/2018 consisting of 29 students. Data analysis technique used is descriptive analysis. The findings show that students' confidence in mathematics in the first cycle reached 10.3% for high category, 55.2% for moderate, and 34.5% for low category. Meanwhile, in the second cycle students' self-confidence score on mathematics reached 6.9% for very high category, 72.41% for high category, and 20.69% for moderate. This study indicates that there is an increase of students' self confidence in mathematics due to CTL approach (REACT).